Functional expression of the catalytic domains of two cysteine proteinases from Trypanosoma congolense - Boulange, A.F.; Serveau, C.; Brillard, M.; Minet, C.; Gauthier, F.; Diallo, A.; Lalmanach, G.; Authié, Edith (Elsevier, 2001)
The catalytic domains of two closely related cysteine proteinases (CP l and CP2) from Trypanosoma congolense, referred to as Cl and C2, were expressed as proforms in Escherichia coli (C 1) and in the baculovirus system (C I and C2). While the bacterial expression system did not allow recovery of active C 1, the baculovirus system led to secretion of inactive zymogens which could be processed at acidic pH into mature enzymes. Active Cl and C2 were purified from serum-free culture supernatants by anion-exchange chromatography and characterised. Their kinetic parameters and pH activity profiles confirmed the relatedness between C2 and native CP2 (congopain). These properties also underline major functional differences between Cl and C2, that appear to relate to discrete but essential sequence differences. It is likely that these two enzymes perform distinct roles in vivo, in the parasite and/or in the host-parasite relationships.